KEBIJAKAN PEMERINTAH DAERAH KABUPATEN KARIMUN TENTANG RELOKASI PASAR (STUDI KASUS RELOKASI PASAR PUAKANG KE PASAR PUAN MAIMUN TAHUN 2012-2013) - Muhammad Ifaundra; Erman Mochtar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The principle of autonomy as stipulated in Law No. 32 of 2004 was autonomous real and responsible and the right choice to increase the degree of social justice and the distribution of authority in Proportional between the central government, provincial government and district / city governments in determining Public Policy, control of economic assets and politics as well as setting local resources, the Government of Karimun Regency create market Relocation Policy aims to increase people's economy. The purpose of this study was to determine the market Relocation Policy. This research out in the district in the department of cooperatives Karimun especially smal and medium enterprises, Trade and Industry And Local Company Karimun, where the informants in this study was head of Trading, Head of Unit Market Local Company Karimun, Head of General and Personnel Company region, Head of Market Development, Distribution of Goods and Services, community leaders, the media and traders. In collecting the data obtained from the documentations and interview to the informant. After the data collected then analyzed using qualitative descriptive analysis.After doing research, Local Government Policy Karimun About Relocation Puakang market to market is not maximized Puan Maimun implemented by local governments, Judging from the information. lack of clarity in the technical guidance and implementation guidelines on Policy and Communication is the submission or delivery of a message from the government to the public, efforts Budgeting great and is not concerned about the development, management and preservation of the market, Management Policy The market does not have the clarity, Form Socialization minimal and not directly to the public.Key words : Public Policy, Implementation, Market Relocation